2013
DOI: 10.5772/55478
|View full text |Cite
|
Sign up to set email alerts
|

Bluetooth Platform for Wireless Measurements Using Industrial Sensors

Abstract: The past decade has seen significant advancement in the field of mobile devices. Various smart devices such as cellular phones, tablets and PDAs have become universal tools in our everyday lives. Their versatility is based on their computing power, portability and their integration with other devices and services such as the World Wide Web. However, these smart devices have an even wider usability spectrum. They can also be used for wireless industrial measurements using existing sensors. The wireless connecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The capabilities offered by wireless communication -such as the iPhone -have played a key role in the fast rate of IT adoption rate. Tasner et al [1] showed that still further improvements are possible. They argue that improved connectivity will open the door for higher levels of data transfer efficiency, data processing, evaluation and logging.…”
Section: Introductionmentioning
confidence: 99%
“…The capabilities offered by wireless communication -such as the iPhone -have played a key role in the fast rate of IT adoption rate. Tasner et al [1] showed that still further improvements are possible. They argue that improved connectivity will open the door for higher levels of data transfer efficiency, data processing, evaluation and logging.…”
Section: Introductionmentioning
confidence: 99%